Topical tacrolimus as treatment of atopic dermatitis - Masutaka Furue; Satoshi Takeuchi (Dove Medical Press, 2009)
Masutaka Furue, Satoshi TakeuchiDepartment of Dermatology, Faculty of Medical Sciences, Kyushu University, Fukuoka, JapanAbstract: Atopic dermatitis (AD) is a common, chronic, relapsing, severely pruritic, eczematous skin disease. The mainstays of treatment for AD are topical tacrolimus and topical steroids. Tacrolimus, a calcineurin inhibitor, not only complements existing treatment options but also overcomes some of the drawbacks of topical steroid therapy when given topically and thus meets the long-term needs of patients in preventing disease progression. Topical tacrolimus has been widely recognized in terms of its short- and long-term efficacies and safety, and it is also accepted as a first-line treatment for inflammation in AD. The recent proactive use of topical tacrolimus may emphasize a long-term benefit of this calcineurin inhibitor for AD treatment. To reduce possible long-term adverse effects, it is important to monitor its topical doses in daily clinics.Keywords: atopic dermatitis, topical tacrolimus, topical steroids, dose, proactive use, adverse effects